ANALISIS MOTIVASI BELAJAR SISWA MELALUI PERTUNJUKAN SENI TARI PADA SISWA KELAS V SD NEGERI 107417 SEI MERAH - Dwi Putri Dina Saharani Putri; Putra Afriadi; Laurensia Masri Perangin Angin; Sri Mustika Aulia; Waliyul Maulana Siregar (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study aims to investigate students’ learning motivation through dance performances in Grade V at SD Negeri 107417 Sei Merah. The background of this research is the low learning motivation among students, indicated by a lack of participation and enthusiasm during lessons, especially in dance classes. This study employed a descriptive quantitative method using purposive sampling. The sample consisted of 1 teacher and 12 fifth-grade students. Data were collected through observation, interviews, documentation, and a questionnaire consisting of 20 statement items. The data were analyzed using descriptive statistical techniques in the form of percentages. The results showed that students’ learning motivation was categorized as "very good" with an average overall score of 84.58%. This reflects that dance performances can enhance students' enthusiasm, self-confidence, cooperation, and perseverance in the learning process. The teacher also noted positive changes in students’ discipline and social interactions after participating in dance activities. Thus, it can be concluded that dance performances contribute positively to improving the learning motivation of Grade V students at SD Negeri 10741 7 Sei Merah and can serve as an effective and enjoyable learning method.